Zola and the Serial Killer: Robert Black and La Bête Humaine - Lynes, Adam; Wilson, David; Jackson, Craig (International Journal of Criminology and Sociology, 2012)
This article presents a critical analysis of Emile Zola’s Le Bête Humaine – a critical analysis which forms the basis of a case study of the real-life, British serial killer Robert Black. The fictional character of Jacques Lantier, a train driver living in France in the late 19th century, who is plagued by thoughts of committing murder is compared to Black - a former PDS van driver - who has been convicted of murdering four young girls between 1981 and 1986. The article explores Zola’s comments and warnings about the relationship between civilisation and the ever-advancing technology that it creates in order to better the human species or, as is the case of Lantier and Black, for the worse